Plaque regression and progenitor cell mobilization with intensive lipid elimination regimen (PREMIER) trial design. Issue 2 (4th October 2013) - Banerjee, Subhash; Abu Fadel, Mazen; Sarode, Ravi; Terada, Lance; Moritz, Thomas; Luo, Ping; Hastings, Jeffrey; Brilakis, Emmanouil S.; Reda, Domenic
<x xml:space="preserve">Abstract</x> Progression of lipid rich necrotic core elements of atherosclerotic vulnerable plaque (VP) or its rupture leads to a majority of cardiovascular events. Endothelial progenitor cells (EPC) contribute to vascular healing and play a crucial role in repair following ischemic injury primarily by endothelialization of VP and neovascularization of ischemic myocardium. We present the rationale and design of the Plaque Regression and Progenitor Cell Mobilization with Intensive Lipid Elimination Regimen or the PREMIER Trial, which is designed to address the question for the very first time whether a highly intensive low‐density lipoprotein (LDL)‐lowering therapy with LDL‐apheresis could lead to a more rapid and detectable reduction in coronary atheroma volume, along with a robust mobilization of EPC compared to standard statin therapy, in patients selected for percutaneous coronary intervention for an acute coronary syndrome. J. Clin. Apheresis 29:97–106, 2014. © 2013 Wiley Periodicals, Inc.